Contrast-enhanced photoacoustic imaging in the second near-infrared window using semiconducting polymer nanoparticles - Upputuri, Paul Kumar (2018)
Photoacoustic imaging (PAI) is a fast growing deep-tissue imaging modality. However, light scattering and absorption in biological tissues limit imaging depth. Short near-infrared wavelengths (650 to 950 nm) are widely used for PAI. Using longer near-infrared wavelengths reduces scattering. We demonstrate deep-tissue contrast-enhanced in vivo photoacoustic imaging at a wavelength of 1064 nm. An ultranarrow bandgap semiconducting polymer poly (thienoisoindigo-alt-diketopyrrolopyrrole) (denoted as PIGD) is designed and demonstrated for imaging at 1064 nm. By embedding colloidal nanoparticles (NPs) of PIGD in chicken-breast tissue, an imaging depth of ∼5  cm is achieved. Intravenous injection of PIGD NPs in living rats showed brain vascular images with ∼2 times higher contrast compared with the brain vascular images without any contrast agent. Thus, PIGD NPs as an NIR-II contrast agent opens new opportunities for both preclinical and clinical imaging of deep tissues with enhanced contrast.